The Impacts of Hazardous and Toxic Waste Management: A Systematic Review - Exposto, Levi Anatolia S.M.; Sujaya, I Nengah (Interdisciplinary Social Studies, 2021)
Looking at the environmental and health problems caused by the irregular disposal of hazardous and toxic waste, it is important to manage B3 waste to prevent and overcome environmental pollution or damage caused by B3 waste and to restore the quality of the polluted environment so that it is following function back. In this case, every activity related to B3 must pay attention to environmental aspects and maintain environmental quality in its original condition and prevent disease. The main objective of this review is to identify and understand the impact of hazardous and toxic waste management. his review was conducted based on sources from Google Scholar, Pubmed, Emerald Insight, DOAJ with the types of journals published such as ELSEVIER, IJSDGE, PROCEEDINGS, ICCEM, HINDAWI, JPHE, JSTFT, JET, AJEST, JCH, WMR, BMC Health Services research and two reports from WHO (World Health Organization). Furthermore, screening of titles, abstracts, and content selection or content according to inclusion and exclusion was carried out which obtained 14 articles that were analyzed further. B3 waste management that enables sorting, storage, transportation, and processing at the final waste disposal site is one of the important strategies in B3 waste management.